Development of equilibrium model of vacuum distillation for benzene/toluene separation using mosaic software - Mohammad Firdaus, Sahda (2015)
This paper presents development of equilibrium model of vacuum distillation for benzene/toluene separation using MOSAIC software. The vacuum distillation process was modeled using MOSAIC software by key in the relevant equations and functions that related to vacuum distillation. The generated code from MOSAIC then transferred to MATLAB® environment to get the data for plotting the graph of temperature and composition profiles of vacuum distillation. The range of temperature in the vacuum distillation column was from 299 K to 318 K. The separation of benzene and toluene using vacuum distillation produce high purity of benzene at distillate which was 85 % of vapour mole fraction at distillate stream. Meanwhile, 92% of vapour mole fraction at bottom stream was toluene.